2012
DOI: 10.1016/j.bbrc.2012.06.141
|View full text |Cite
|
Sign up to set email alerts
|

The flexibility of two tropomyosin mutants, D175N and E180G, that cause hypertrophic cardiomyopathy

Abstract: Point mutations targeting muscle thin filament proteins are the cause of a number of cardiomyopathies. In many cases, biological effects of the mutations are well-documented, whereas their structural and mechanical impact on filament assembly and regulatory function is lacking. In order to elucidate molecular defects leading to cardiac dysfunction, we have examined the structural mechanics of two tropomyosin mutants, E180G and D175N, which are associated with hypertrophic cardiomyopathy (HCM). Tropomyosin is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 17 publications
2
46
0
2
Order By: Relevance
“…Hence, mutations associated with charge changes at these sites (e.g. at residues 70, 91, 168, 175, 180) may increase local coiled-coil flexibility, and thus modify tropomyosin position on actin filaments [32, 33]. This could amplify effects noted above that weaken actin-tropomyosin interaction and thereby exacerbate aberrant responses to troponin and myosin.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, mutations associated with charge changes at these sites (e.g. at residues 70, 91, 168, 175, 180) may increase local coiled-coil flexibility, and thus modify tropomyosin position on actin filaments [32, 33]. This could amplify effects noted above that weaken actin-tropomyosin interaction and thereby exacerbate aberrant responses to troponin and myosin.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al found that the tropomyosin coiled-coil is rather stiff with a persistence length about 12 times its own length (108,(134)(135)(136)(137)199). Thus, local troponin-and myosininduced shifts of semirigid tropomyosin on the actin filament can be expected to be propagated along the tropomyosin cable with limited decrement, producing expected filament cooperative effects.…”
Section: Gestalt Binding Of Tropomyosin On F-actinmentioning
confidence: 93%
“…Therefore each successive actin subunit along F-actin is matched to a tropomyosin pseudorepeat (138). Here, roughly 30 electrostatic interactions define the weak actin-tropomyosin electrostatic interactions (7,126,137,138,170). Thus, the charged electrostatic track along actin that attracts tropomyosin does not necessarily define a truly specific axial or azimuthal position for tropomyosin on the track.…”
Section: Gestalt Binding Of Tropomyosin On F-actinmentioning
confidence: 95%
“…Another approach for measuring the bending stiffness of actin filaments is based on the visualization of the filaments subjected to the Brownian bending and data analysis with the WLC theory (9,11,(23)(24)(25)(26)(27). The major parameter in the WLC theory is the persistence length, L p , which is determined by the bending stiffness K and absolute temperature T: L p ¼ K/k B T, where k B is the Boltzmann constant.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…However, these hypotheses were not tested directly. It was shown theoretically (9,10) and experimentally (9,11) that the bending stiffness of a Tpm molecule may be an important parameter in the activation of thin filaments, particularly in the propagation of the mechanical wave of activation along the filament.…”
Section: Introductionmentioning
confidence: 98%